Modulation of TNF-α plasma levels in coronary artery disease [CAD] and non-CAD male patients by lncRNA UCA1 and aspirin - Nowrouzi-Sohrabi, Peyman; Seghatoleslam, Atefeh; Izadpanah, Peyman; Erfani, Mehran; Ahmadvand, Hassan; Kalani, Mehdi (Archives of Biological Sciences, 2020)
Paper description: The expression of long non-coding RNA urothelial carcinoma-associated 1 (UCA1) expression and its association with IL-6, IL-22 and TNF-α in patients with coronary artery disease (CAD) and healthy non-CAD (NCAD) individuals was examined. UCA1 expression in peripheral blood mononuclear cells (PBMCs) and IL-6, IL-22 and TNF-α plasma levels in CAD and NCAD groups were assessed by real-time PCR and flowcytometry, respectively. UCA1 expression was not significantly different between the groups. Its higher level in aspirin users was indirectly associated with a decrease in plasma TNF-α. UCA1 upregulation might be an underlying mechanism for downregulation of TNF-α in aspirin users. Abstract: The aim of this study was to investigate the expression of long non-coding RNA urothelial carcinoma-associated 1 (UCA1) and its role in TNF-α production as one of the main inflammatory cytokines, in peripheral blood mononuclear cells (PBMCs) of patients with coronary artery disease (CAD) and healthy non-CAD (NCAD) individuals as the control group. Fifteen CAD and 15 NCAD individuals were enrolled in the study. UCA1 expression in PBMCs and the plasma concentrations of interleukin (IL)-6, IL-22 and tumor necrosis factor (TNF)-α were assessed by real-time PCR and flowcytometry, respectively. UCA1 expression was not significantly different between the CAD and NCAD groups, however, its level was higher in PBMCs of regular aspirin users of both study groups. Furthermore, aspirin users showed a significantly lower plasma level of TNF-α in comparison to non-aspirin users. In addition, UCA1 expression was negatively correlated with the level of TNF-α in the total sample of the examined population. It seems that the increased levels of UCA1 may be an underlying mechanism for downregulation of TNF-α in aspirin users.